100 years of the clinic and the 140th anniversary of the Department of skin and sexually transmitted diseases of Rostov state medical University - Z. A. Kuzina; O. A. Sidorenko; L. A. Anisimova; E. P. Opruzhenkova; V. A. Grebennikov; V. E. Temnikov; V. V. Starostenko (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article describes the stages of development and formation of the national dermatovenereology, history of one of the oldest department of skin and sexually transmitted diseases in Russia. Discusses national and global role of the P.V. Nikolsky, Z.N. Grjebine, N.A. Torsuev, L.M. Khasabov and other colleagues of clinic and chair in the learning and teaching of dermatology and venerology, their contribution to the fight against leprosy, skin and venereal diseases.